2023
DOI: 10.1093/emph/eoad019
|View full text |Cite
|
Sign up to set email alerts
|

Low birthweight is associated with epigenetic age acceleration in the first 3 years of life

Abstract: Background and objectives The Developmental Origins of Health and Disease (DOHaD) hypothesis posits that early life adversity is associated with poor adult health outcomes. Epidemiological evidence has supported this framework by linking low birthweight with adult health and mortality, but the mechanisms remain unclear. Accelerated epigenetic aging may be a pathway to connect early life experiences with adult health outcomes, based on associations of accelerated epigenetic aging with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Also, birth size may be linked with biological age in healthy adult individuals which in consequence may lead to various risks of chronic disease development. Recent research reported a negative relationship between birth weight and DNA methylation in men but not in women of 20.8–22.5 years 21 or in epigenetic age acceleration over the first 3 years of life 22 . Another study showed contradictory results for various DNA methylation clocks in young and middle-aged adults 23 or no relationship between birth weight and telomere length 24 .…”
Section: Introductionmentioning
confidence: 98%
“…Also, birth size may be linked with biological age in healthy adult individuals which in consequence may lead to various risks of chronic disease development. Recent research reported a negative relationship between birth weight and DNA methylation in men but not in women of 20.8–22.5 years 21 or in epigenetic age acceleration over the first 3 years of life 22 . Another study showed contradictory results for various DNA methylation clocks in young and middle-aged adults 23 or no relationship between birth weight and telomere length 24 .…”
Section: Introductionmentioning
confidence: 98%